Design and simulation of a modified block transmission system with pre-coding - Khatib, M.; Farid, Ghani, Prof. Dr.; Ain, M. F. (Institute of Electrical and Elctronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/